Economic theory and operations analysis - Baumol, William J. (New Delhi : Prentice-Hall of India, 2000)
Economics
Keywords: Economic theory; Programming; Operations analysis; Duality; Production; Consumers; Firm; Market structure; Game theory; Welfare economics; Capital; Investment